2017
DOI: 10.1007/s11255-017-1554-6
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-to-lymphocyte ratio as an independent predictor for survival in patients with localized clear cell renal cell carcinoma after radiofrequency ablation: a propensity score matching analysis

Abstract: High preoperative neutrophil-to-lymphocyte ratio and elevated postoperative neutrophil-to-lymphocyte ratio are associated with significant increase in risk of local recurrence as well as distant metastasis. The combination of neutrophil-to-lymphocyte ratio with the other prognostic indicators can be applied in the evaluation of relapse risk in patients with clear cell renal cell carcinoma after radiofrequency ablation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 27 publications
1
19
0
Order By: Relevance
“…A summary of 18 recent studies investigating the prognostic role of NLR in RCC is shown in Table . A total of 10 studies included mainly metastatic patients; in eight studies, the main treatment was molecular‐targeted agents; and in two studies, the treatment was cytoreductive nephrectomy.…”
Section: Differential Blood Cell Markersmentioning
confidence: 99%
See 2 more Smart Citations
“…A summary of 18 recent studies investigating the prognostic role of NLR in RCC is shown in Table . A total of 10 studies included mainly metastatic patients; in eight studies, the main treatment was molecular‐targeted agents; and in two studies, the treatment was cytoreductive nephrectomy.…”
Section: Differential Blood Cell Markersmentioning
confidence: 99%
“…Furthermore, post‐treatment NLR was a significant prognostic factor of CSS. Another study of post‐treatment changes in NLR was carried out by Chang et al . They analyzed the association among preoperative NLR, postoperative change in NLR and survival in patients who underwent radiofrequency ablation for localized RCC.…”
Section: Differential Blood Cell Markersmentioning
confidence: 99%
See 1 more Smart Citation
“…Elevated neutrophil-to-lymphocyte ratio (.5) is an independent predictor of worse survival in patients who undergo 90 Y TARE for colorectal metastases in liver (102). High preoperative neutrophil-to-lymphocyte ratio (.2.79) and elevated postoperative neutrophil-to-lymphocyte ratio was associated with a significant increase in risk of local recurrence and distant metastasis after RFA of renal cell cancer (103). However, lymphocyte-to-monocyte ratio is predictive of survival after RFA for colorectal liver metastases (104).…”
Section: Combining Io Therapies With Immunotherapymentioning
confidence: 99%
“…28 Decreased post-RFA neutrophil-lymphocyte ratio (NLR) was associated with improved disease-free survival in 178 small hepatocellular carcinoma (HCC) patients, 29 while increased postablation NLR was associated with local recurrence and metastatic disease in patients with 185 renal cell carcinoma (RCC) patients treated with RFA. 30 Additionally, an increase in the number of interferon gamma (IFN-γ) producing cytotoxic natural killer (NK) cells was associated with longer disease-free survival after RFA in 37 subjects with HCC. 31…”
Section: Cellular Injury and Immunogenicity Of Thermal Ablative Therapymentioning
confidence: 99%